A rapid discriminative hydrogen–deuterium exchange and LC-HRMS/MS strategy for primary and higher order structural mapping of therapeutic proteins: a case study using filgrastim. Issue 12 (7th March 2023) - Thakkar, Harsh; Eerla, Rameswari; Sharma, Lokesh; Shah, Ravi P.
Abstract : Amalgamation of hydrogen–deuterium exchange and mass spectrometer for rapid determination of higher order structural differences in therapeutic proteins. Abstract : A vast number of therapeutic proteins are approved and available on the market. However, there are very limited analytical approaches available for the rapid determination of primary and higher-order structures which can be utilized for counterfeit identification. In the present study, filgrastim biosimilar products from different manufacturers were considered for developing discriminative orthogonal analytical techniques to determine structural variations. The developed intact mass analytical method and peptide mapping through LC-HRMS were able to differentiate three biosimilars based on deconvoluted mass and possible structural modification, respectively. Another structural attribute employed was charge heterogeneity through isoelectric focusing, which provides a snapshot of the presence of charge variants/impurities and was able to differentiate various marketed formulations of filgrastim. These three techniques can certainly differentiate the products that contain counterfeit drugs due to their capability concerning selectivity. Additionally, a unique HDX technique on LC-HRMS was developed, which can determine the labile hydrogen exposed to deuterium exchange in a specified time. HDX aids in identifying the workup process or changes in the host cell in the counterfeit product by differentiating the protein based on its higher-order structure.